PENGARUH PENERAPAN LKS BERORIENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM-ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR IPA FISIKA SISWA KELAS VIII SMPN 3 RANAH PESISIR - Nurfah Wilda; Hufri Hufri; Fatni Mufit (PILLAR OF PHYSICS EDUCATION, 2015)
The low scores of the students of SMPN 3 Ranah Pesisir in Physics were caused by the lack of their activeness and  interaction in learning process. One effort to help the students to solve these problems was by applying LKS that is TAI-oriented learning model. Based on the problems above the study whose purpose was to find out the effect of TAI-oriented learning model had been conducted toward the scores of the second year students of SMPN 3 Ranah Pesisir  in Physics. The research design used was Quasi Experimental, using Randomized Control Group Only Design. The population of this research was the second year students of SMPN 3 Ranah Pesisir who were registered in the academic year 2014/2015, while the samples were selected by using purposive sampling technique. The data involved the students’ scores in cognitive, affective and  psychomotor domains. The data from those three domains were analyzed by using t-test. The score of experiment class in cognitive domain was 88.38, higher than control class, 80.01. The score of experiment class in affective domain was73.94, and the control class was 63.58. Further, the score of experiment class  in psychomotor domain was 88.91, higher than control class, 80.89. After applying t-test to the three domains, then, the hypothesis could be accepted. It can be concluded that there is a significant effect of using LKS that is TAI-oriented learning model toward the scores of the second year students of SMPN 3 Ranah Pesisir in Physics, on the degree of 0.05